Centralising space: the physical education and physical activity experiences of South Asian, Muslim girls. Issue 5 (3rd July 2016) - Stride, Annette
Abstract : This paper explores the physical education (PE) and physical activity experiences of a group of South Asian, Muslim girls, a group typically marginalised in PE and physical activity research. The study responds to ongoing calls for research to explore across different spaces in young people's lives. Specifically, I draw on a 'middle-ground' approach, using Hill Collins' matrix of domination and the notion of intersectionality. These concepts offer the possibility to explore the kinds of settings (physical, social and cultural) in which girls undertake PE and physical activity, how these spaces influence experience and how the girls navigate these spaces. The study is based in a large, urban, co-educational, secondary school in Yorkshire, England (95% of the students are from minority ethnic communities, 91% are Muslim and 63% live in the top 10% most deprived neighbourhoods in the country). Data generation involved three phases: observations, creating research artefacts in focus groups and in-depth interviews. The findings reveal the diverse ways the girls are physically active. They also demonstrate a complexity to their involvement which is contingent upon space, discourses and people. For example, discourses of competition, ability and peers are more significant within PE; whilst family, religion and culture feature beyond this context. The paper concludes by acknowledging the girls' heterogeneity and agency in the ways they strategically navigate spaces in their quest to be physically active on their terms.